Association of Nutritional Status with Quality of Life in Breast Cancer Patients on Chemotherapy - Muhammad, Nanda Noor; Aziza, Aziza (Muhammadiyah Medical Journal, 2024)
Background: Cancer patients often experience a decline in their nutritional status due to chemotherapy, which can result in malnutrition and negatively impact their quality of life. However, there has been limited research on the prevalence of these conditions in breast cancer patients undergoing chemotherapy in Indonesia. Purposes: This research aims to explore the connection between the quality of life and the nutritional status of breast cancer patients receiving chemotherapy treatment. Methods: A cross-sectional study was conducted in a private hospital in Pekanbaru using non-probability sampling. Demographic profile, nutritional status assessment by PG-SGA, and quality of life assessment by the EORTC QLQ C-30 module were obtained. Mann-Whitney and Spearman's tests analyzed the association between nutritional status and QoL. Results: The average age of breast cancer patients was 45.46±14.375. The prevalence of overweight and obesity was 64.1%. According to the PG-SGA score, the vast majority of patients, approximately 91%, were discovered to be well-nourished. The nutritional status was significantly associated with most functional and symptom scales (p0.05). Improved nutritional status is associated with increased functionality and a reduction in symptoms, while malnutrition has been linked to decreased quality of life across multiple dimensions. Conclusion: The nutritional status of breast cancer patients affects some dimensions of quality of life. Well-nourished patients had better function and fewer symptoms.